PERAN GURU DALAM PEMBELAJARAN - Ranto Hutabarat; Jenni Asri; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
The role of teachers in education is crucial and multifaceted. Teachers not only act as knowledge facilitators but also as mentors, motivators, and role models for students. As facilitators, teachers manage and deliver instructional content in engaging and relevant ways, helping students grasp necessary concepts and skills. As mentors, they provide individualized guidance and support, tailoring their teaching approaches to meet the diverse needs and abilities of each student. In their motivational role, teachers encourage students to stay motivated and enthusiastic about learning, creating a positive and inclusive learning environment. Additionally, teachers serve as role models, demonstrating the values and behaviors expected through their daily actions and interactions. Thus, teachers play a key role in developing students' potential, facilitating academic achievement, and shaping their character and social skills essential for their future lives.